(untitled) (Third Sector Social Economic Review, 2026)
Environmental disasters resulting from global warming and current geopolitical events inevitably affect both the energy and economic strategies of countries. Consequently, factors such as energy independence and low costs are further fueling the transition to sustainable and renewable energy. Today, the trend toward wind energy, one of the renewable energy sources, is increasing due to factors such as lower cost, ease of use, abundance, and inexhaustibility. In this context, this study examines the relationship between FD and GPR and wind energy for the countries with the highest wind energy production: China, the USA, Germany, the UK, India, Spain, France, Canada, and Sweden. The study covers the period 2001-2021. Necessary priori tests are performed to peruse the long-term cohesion of the variables in the model. Westerlund and Edgerton (2008) panel cointegration test is enforced. The panel cointegration test results indicate that the variables move together in the long term. Long-term coefficient estimates were subsequently performed, finding that FD has a surprisingly negative impact on wind energy production in China, the US, India, and Sweden. In France, the impact is notably positive. GPR has a positive impact on wind energy in Sweden but a negative impact in China and France.